Acuerdos Mercosur-Unión Europea desde la perspectiva de la política exterior Argentina - Simonoff, Alejandro (2020)
El presente articulo busca comprender, mediante el ultimo impulso al proceso de negociacion entre el Mercosur y la Union Europea llevado adelante durante la Presidencia de Mauricio Macri (2015-2019), cuales fueron los rasgos fundamentales de la estrategia de relacionamiento externo del Gobierno conservador argentino. Para ello, se ha utilizado una metodologia cualitativa recurriendo a fuentes oficiales, reportajes y notas periodisticas que permitieron entrever el proceso de negociacion. Se ha podido concluir que ademas de la voluntad argentina para que la llegada del acuerdo fuese posible, debio producirse el cierre del ciclo progresista, sobre todo desde la destitucion de Dilma Rousseff, hecho que puso en sintonia al Mercosur para llevarlo adelante. En el intercambio de compromisos quedo claro que el Gobierno argentino estuvo dispuesto a abandonar los obstaculos que habian existido desde la ultima posguerra en el intercambio comercial con el Viejo Continente a favor de la creencia en que la apertura generaria crecimiento. De las acciones que culminaron con el anuncio de las negociaciones para la firma del Acuerdo en 2019, se pudo observar las limitaciones de la administracion a la hora de comprender como funcionaba el sistema internacional, permitiendo tambien evaluar las caracteristicas de su modelo de insercion.
The present article attempts to understand the central features of the foreign strategy of Mauricio Macri´s conservative Argentinian government (2015-2019). A close scrutiny of the final drive to successfully conclude negotiations between Mercosur and the European Union during the closing stages of Mr.Macri´s administration is performed. A qualitative method has been used, based on a detailed inspection of official sources, press reports and news stories covering the talks. It is possible to conclude that besides the Argentinian decision to go ahead with the talks and bring them to a positive conclusion, it was also necessary for the "Progressive" cycle in regional politics, to come to an end. This was greatly expedited by the impeachment of former Brazilian President Dilma Roussef, a development that allowed all Mercosur countries to be in the same page regarding the organization´s relationship with the European partners. The final outcome of the talks made it clear that the Argentinean government had finally accepted to remove all the obstacles that had obstructed its trade with Europe during the post-war period. Instead, a new approach was adopted, based on the belief that free trade would promote enhanced economic growth. The actions undertaken by the Macri administration leading into the opening of the dialogs resulting in the 2019 Agreement, underscore the limitations of his government in grasping the workings of the international system. Finally, this allows to reach a better understanding the main features of the Argentinean model of insertion in the world economy.
Keywords: Argentina; Autonomía; Dependencia; Mercosur; Política exterior; Unión Europea; Argentina; Autonomy; Dependency; Mercosur; Foreign policy; European Union